Paheman Radyapustaka sebagai Skriptorium - Ahmad Alfan Rizka Alhamami (Masyarakat Pernaskahan Nusantara, 2020)
Since its establishment on October 28, 1890, Paheman Radyapustaka has only been known for its function as a museum. The main activity of Paheman Radyapustaka is as a place for writing, copying, and collecting Surakarta manuscripts, so that Paheman Radyapustaka deserves to be called a Scriptorium. This paper aims to reveal the production activities of the Paheman Radyapustaka scriptorium which includes the writers/copyists, the writing results, and the genre. The method in this paper is a method of codicological studies that includes history, writers/copyists, and scriptorium collections. The results of the search through the archives and manuscript colophon of the Paheman Radyapustaka scriptorium were that of the 400 manuscripts in his collection, there were 82 manuscripts written by the Scripts of the Scriptures. The scribes of the Paheman Radyapustaka Scriptorium were Wirapustaka, Sastrasayana, Dayapangreka, Karyarujita and the residents. The genres written by the scribes of the Paheman Radyapustaka scriptorium are macapat and gancaran. === Sejak berdiri pada 28 Oktober 1890, Paheman Radyapustaka hanya dikenal fungsinya sebagai sebuah museum. Aktivitas utama dari Paheman Radyapustaka adalah sebagai tempat penulisan, penyalinan, dan pengoleksian naskah-naskah Surakarta sehingga Paheman Radyapustaka pantas disebut sebagai Skriptorium. Tulisan ini bertujuan untuk mengungkap aktivitas produksi naskah Skriptorium Paheman Radyapustaka yang meliputi para penulis/penyalin, hasil penulisan, dan genrenya. Metode dalam tulisan ini adalah metode kajian kodikologi yang mencakup sejarah, penulis/penyalin, dan koleksi skriptorium. Hasil penelusuran melalui arsip dan kolofon naskah Skriptorium Paheman Radyapustaka adalah dari 400 naskah koleksinya terdapat 82 naskah yang ditulis oleh para juru tulis Skriptorium. Para juru tulis Skriptorium Paheman Radyapustaka adalah Wirapustaka, Sastrasayana, Dayapangreka, Karyarujita dan para warga. Genre yang ditulis oleh para juru tulis Skriptorium Paheman Radyapustaka adalah macapat dan gancaran.